A multifaceted intervention for evidence-based pressure ulcer prevention: a 3 year follow-up. Issue 4 (10th December 2020) - Sving, Eva; Fredriksson, Lennart; Mamhidir, Anna-Greta; Högman, Marieann; Gunningberg, Lena
ABSTRACT: Aim: To assess sustainability of an intervention used to implement pressure ulcer prevention. Background: The Promoting Action on Research Implementation in Health Service, framework was used to develop an intervention aimed to implement evidence-based pressure ulcer prevention in a hospital setting. A short-term follow-up showed that significantly more patients received pressure ulcer prevention. A qualitative process evaluation gave support that the intervention and the implementation process changed the understanding and approach to working with pressure ulcer prevention from treating to preventing. Method: The study had a sequential mixed method approach, combining quantitative and qualitative data. For the quantitative data, baseline and short-term follow-up (6–8 months) data reported in an initial study were compared with long-term follow-up (36–42 months) data ( n = 259 patients). For the qualitative data, interviews with registered nurses ( n = 20), assistant nurses ( n = 7) and first-line managers ( n = 5) were performed. Results: The performance of pressure ulcer prevention was sustained 3 years from its conception. The number of patients with pressure ulcers was reduced ( P = 0.021). Systematic work with quality measurements, support from first-line managers, internal facilitation, collaboration and pressure ulcer prevention skills could explained the sustainability. Obstacles to achieve high-quality pressure ulcer prevention were inadequate communication, high workloads and high rates of new and substitute nurses. Conclusion: Three different components for sustainability on the micro-level are described; benefits for the patients, the need for routinization and development over time. Threats to sustainability are described as factors on the macro-level. There needs to be collaboration in the healthcare organization from the micro-to-macro levels, and committed experienced nurses are needed to obtain high-quality sustainable pressure ulcer prevention.